Uwagi ikonograficzne na temat medali ślubnych Fryderyka Augusta Wettyna i Marii Józefy Habsburg z okazji Festiwalu Planet w Dreźnie (od 10 do 26 września 1719 roku) - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2022)
In the course of preliminary research, the author managed to locate most of the engravings by artists associated with the Dresden court: Oluf Wif, Johann August Corvinus and Carl Heinrich Jacob Fehling, whose work drew thematically on the reverses of the medals which commemorated the Festivaof the Planets in Dresden. These finds are the main subject of interest in this paper. The compositional relationship between medallic art and engraving is, in most cases, indisputable. It should be noted, however, that the medallist, having to reproduce a much larger engraving on a medal disc, was compelled to reduce many details that the engraver had so meticulously captured. Nevertheless, the inspiration with the engraving yielded works which are unique and extraordinary in terms of expression and content.